2013
DOI: 10.1002/adma.201302439
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility, Aligned Crystalline Domains of TIPS‐Pentacene with Metastable Polymorphs Through Lateral Confinement of Crystal Growth

Abstract: Patterns composed of solvent wetting and dewetting regions promote lateral confinement of solution-sheared and lattice-strained TIPS-pentacene crystals. This lateral confinement causes aligned crystal growth, and the smallest patterns of 0.5 μm wide solvent wetting regions promotes formation of highly strained, aligned, and single-crystalline TIPS-pentacene regions with mobility as high as 2.7 cm(2) V(-1) s(-1) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
165
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(168 citation statements)
references
References 39 publications
3
165
0
Order By: Relevance
“…Therefore, many efforts have aimed to exploit the direction-controlled dewetting by adjusting the moving directions of the upper or bottom substrates or by modifying the substrate surfaces using special treatments. [12][13][14][15][16][17] For example, Bao and co-workers developed a series of techniques, including shearing and coating, to deposit aligned crystalline thin films; however, these procedures more or less rely on the nanostructures of the shearing blade or of the modified substrate, which are rarely involved in large-scale implementation. [14][15][16] Jiang et al recently reported that a line-pillarstructured template could be employed to guide 3D dewetting to position crystal stripes, but the preparation and removal of the template would probably complicate device fabrication, which would eventually render the scaled-up process more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have aimed to exploit the direction-controlled dewetting by adjusting the moving directions of the upper or bottom substrates or by modifying the substrate surfaces using special treatments. [12][13][14][15][16][17] For example, Bao and co-workers developed a series of techniques, including shearing and coating, to deposit aligned crystalline thin films; however, these procedures more or less rely on the nanostructures of the shearing blade or of the modified substrate, which are rarely involved in large-scale implementation. [14][15][16] Jiang et al recently reported that a line-pillarstructured template could be employed to guide 3D dewetting to position crystal stripes, but the preparation and removal of the template would probably complicate device fabrication, which would eventually render the scaled-up process more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, to obtain solution-processed films with highly ordered crystal structure, novel printing processes have been reported that focus on the behavior of molecules in drying solutions. [14][15][16][17] In addition, simple treatments under solvent vapor after film fabrication are also effective for improving the crystallinity [18][19][20][21] and the size of the domains in the films. [21][22][23][24][25] Although effects of solvent vapor on transitions of crystal structures are also prospective, detailed studies of the transitions of crystal structures have not been conducted.…”
mentioning
confidence: 99%
“…C Guided crystallization of solution-processed organic semiconductor thin films via substrate patterning can enable the control of material properties with fine spatial resolution and be used to preferentially orient molecules along a given direction. 1,2 Potential applications of guided crystallization on pre-specified templates include the fabrication of patterned optical coatings or conductive paths with arbitrary shapes 1 as well as dense arrays of organic thin-film transistors. 2 In addition, the ability to control the alignment of organic semiconductor small molecules has been employed to study the effect of grain boundary orientation mismatch on electrical properties.…”
mentioning
confidence: 99%
“…1,2 Potential applications of guided crystallization on pre-specified templates include the fabrication of patterned optical coatings or conductive paths with arbitrary shapes 1 as well as dense arrays of organic thin-film transistors. 2 In addition, the ability to control the alignment of organic semiconductor small molecules has been employed to study the effect of grain boundary orientation mismatch on electrical properties. 3 Due to its limited intermolecular interactions, the small molecule organic semiconductor triethylsilylethynyl anthradithiophene (TES ADT) can be deposited in a thin film with an essentially disordered state and then be made to crystallize in the form of spherulites upon exposure to solvent vapor.…”
mentioning
confidence: 99%
See 1 more Smart Citation